Experiences of Afghan-Canadian language and cultural advisors who served with Canadian forces abroad: an interpretive phenomenological analysis - Mercier, Jean-Michel; Carmichael, Victoria; Dupuis, Gabrielle; Mazhari, Sayed Ahmad Zia; Fatimi, Yahseer; Laidler, Tim; Hosseiny, Fardous (Frontiers in Communication, 2024)
Though much research has been conducted on the potential well-being effects of deployment on armed forces members, a significant gap seems to exist in the literature when it comes to its effect on conflict-zone interpreters. Drawing on the experiences of six former Afghan-Canadian Language and Cultural Advisors (LCAs), this paper aims to contribute to expanding the nascent literature on conflict-zone interpreters by exploring how former LCAs perceive their experiences before, during, and after their deployment and the resulting impacts on their well-being. Interested in an in-depth exploration of the experiences of former LCAs, this study employed an interpretive phenomenological analysis (IPA) approach. Through the analysis, four superordinate themes emerged in participants' narratives including: 1) the right opportunity, referring to the reasons for becoming an LCA; 2) overcoming challenges, when it comes to the work itself; 3) deserving better, relating to the experience returning to post-service life; and 4) moving forward, speaking to the current reality of participants. The results reveal key insights into the unique experiences and support needs of former Afghan-Canadian LCAs included in the study, offering an in-depth account of their experience before, during and after their service. The findings also offer important considerations regarding the support available not just to interpreters but to all contractors deployed in conflictzones.